Satellite-only Versus Combined High Degree Global Geopotential Model Tailored to Gravity Field in Egypt, Using Integral Formulas - Amin, Maher M.; Refaat, Mervat M.; Ruby, Abd-Elrahim (IJRDO-Journal of Applied Science, 2017)
Global Geopotential Models (GGMs) may contain long-wavelength errors due to difficulties in collecting and using global heterogeneous gravity data, which further degrades the quality of regional gravity field modelling. In this study, satellite-only and high degree reference geopotential models denoted as GOCO05s and EGM2008, respectively, have been tailored (refined) to fit the gravity data in Egypt using integral formulas in order to select the optimal model that can be used for the reference gravity field model for the Egyptian territory. The results show that the tailored model of EGM2008 denoted as EGTM0817 is the one that gives better results in Egypt than the other tailored model of GOCO05s denoted as EGTGOC5s, where the mean value, the standard deviation and the range of the reduced gravity anomalies to EGTM0817 compared with EGTGOC5s have lesser values by about 80%, 30%, and 21%, respectively.